PENGGUNAAN WHATSAPP DAN INSTAGRAM TERHADAP MINAT BELAJAR PENDIDIKAN AGAMA ISLAM DI SMAN 1 PINRANG - Musra, Fauziyyah; Rapi, Muh; Syamsuddin, Syamsuddin; Huda, Khairul (Istiqra: jurnal hasil penelitian, 2022)
This research aims to determine and analyze the influence of the intensity of use of WhatsApp and Instagram in fostering students’ interest in learning at SMAN 1 Pinrang in taking Islamic religious education subjects. This research uses quantitative methods, the subjects of this research are 85 class X students who were selected using a temporary random sample approach. data analysis using multiple regression to solve the problems posed. The results of this research show that the use of WhatsApp and Instagram to get grades for Islamic religious education subjects is divided into three categories, namely medium, high and low. From these results, students must manage their time more effectively, especially when using WhatsApp and Instagram